Камсьор батыр но Инсьор нылаш: литературные сказки / ред.-сост. В.Н.Ившин (для семейного чтения, 2011)
Экземпляры: аб. (20130418) / Инвентарный номер: 1570 / Цена: 47.33 / Авт.знак: К-18 / ГРНТИ: 17 / ББК: 84(2Рос-Удм)